Fermentasi Kopi Robusta (Coffea canephora) Menggunakan Isolat Bakteri Asam Laktat Dari Feces Luwak Dengan Perlakuan Lama Waktu Inkubasi - Doni Usman; Agung Suprihadi; Endang Kusdiyantini (Jurnal Akademika Biologi, 2015)
Coffee is one of Indonesian main corps commodity. Caffeine content of robusta coffee is 1.6%-2.4% higher than arabica coffee that was 0.9-1.2%. Coffee fermentation was one of method to decrease caffeine content. Luwak coffee is coffee that produces by luwak use their digest system in luwak body and defecates as faeces. Lactic acid bacteria (LAB) exploration from luwak faeces that fed by robusta coffee is one of method to get lactic acid bacteria. This research aimed was lactic acid bacteria isolation from luwak faeces and determine best incubation time on robusta coffee fermentation. Bacteria isolation was resulted 27 isolate. Biochemical test done by Gram Staining Test, Catalase Test, Motility Test, and Acid Producing Test and resulted 13 LAB isolate. Characterization test done to all of LAB isolate and resulted best 3 isolate. Isolate M6 was xylanolitic potency, M8 was Proteolytic potentcy and m16 was cellulolytic potency. Robusta coffee fermentation done used mixed of M8, M6 and M16 as inoculum. This research use Complete Random Design (RAL), the treatment was fermentation time 8 hour (D1), 16 hour (D2) and 24 hour (D3), each treatment replays 3 times. Kontrol of this fermentation is robusta coffee without fermentation treatment (control 1) and luwak robusta coffee  (control 2). Data analysed by Analysis of Variance (ANOVA) continuing by Duncan Test with significance rate was 95%. This research result shown that fermentation time duration was cause decrease of caffein content, coffee beans weight and fermentation fluid pH. Highest caffeine content on D1 was 0.95%, and D3 was 0.72 %.Keyword: Luwak faeces, lactic acid bacteria, gram staining, fermentation, exploration